2023
DOI: 10.1177/09567976221141854
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Learned Cognitive Flexibility to Novel Stimuli and Task Sets

Abstract: Adaptive behavior requires learning about the structure of one’s environment to derive optimal action policies, and previous studies have documented transfer of such structural knowledge to bias choices in new environments. Here, we asked whether people could also acquire and transfer more abstract knowledge across different task environments, specifically expectations about cognitive control demands. Over three experiments, participants (Amazon Mechanical Turk workers; N = ~80 adults per group) performed a pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…In particular, Dreisbach and Fröber (2019) argue that some cases of flexibility modulations may depend on concurrent task activation, rather than the adjustment of a general “updating threshold.” Lowering the updating threshold may increase flexibility in general; on the other hand, adaptations based on concurrent task activation may manifest as increased flexibility between only specific tasks held in working memory. When participants can rely on explicit task cues for the upcoming task, they may rely on task-specific flexibility adaptations via such concurrent task-set activation rather than more effortful adjustments to the general updating threshold which may only be necessary in paradigms without explicit task cueing such as Wen et al (2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Dreisbach and Fröber (2019) argue that some cases of flexibility modulations may depend on concurrent task activation, rather than the adjustment of a general “updating threshold.” Lowering the updating threshold may increase flexibility in general; on the other hand, adaptations based on concurrent task activation may manifest as increased flexibility between only specific tasks held in working memory. When participants can rely on explicit task cues for the upcoming task, they may rely on task-specific flexibility adaptations via such concurrent task-set activation rather than more effortful adjustments to the general updating threshold which may only be necessary in paradigms without explicit task cueing such as Wen et al (2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current set of experiments only examined flexibility learning in the context of cued task switching and does not rule out the possibility that cross-task flexibility transfer could occur under other experimental conditions. Specifically, cross-task flexibility transfer was recently demonstrated in a probabilistic version of the Wisconsin Card Sorting Task (Wen et al, 2023). There, participants completed the card sorting task in either high (frequent uninstructed rule switches) or low volatility (infrequent rule switches) environments before transitioning to a medium-volatility transfer phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in addition to there not being a clear theoretical explanation for why that might be the case, prior findings contradict this idea. Wen et al (2023) observed between-task transfer of cognitive flexibility in a probabilistic version of the Wisconsin Card Sorting Test. Participants were required to select a card that had the same value as the reference card in one of four dimensions (color, shape, number, and filling).…”
Section: Between-task Transfer Of Other Types Of Controlmentioning
confidence: 87%
“…We tackled this question by investigating transfer of item-specific control from one task to another task-that is, we asked whether encountering a stimulus feature (i.e., a predictive cue) that became associated with a particular control setting in one task would similarly trigger retrieval and execution of that control setting in a different task. Only one prior experiment has demonstrated such between-task transfer of item-specific control (Ileri-Tayar et al, 2022; see Wen et al, 2023 for transfer of learned cognitive flexibility). Therefore, it is not yet known if the between-task transfer effect is (a) stable (i.e., whether it is replicable) and (b) generalizable (i.e., extends to novel, theoretically motivated conditions) or if there are potential boundary conditions for transfer.…”
mentioning
confidence: 99%